"Canaries in the mine..." the impact of Affordable Care Act implementation on people with disabilities: Evidence from interviews with disability advocates. Issue 1 (January 2018) - Lindner, Stephan; Rowland, Ruth; Spurlock, Margaret; Dorn, Stan; Davis, Melinda
Abstract: Background: The Affordable Care Act (ACA) has many provisions that could improve health care for people with disabilities, including Medicaid expansion and the ability to purchase qualified health plans (QHPs). Objective: To explore how ACA provisions affected people with disabilities' health care experiences during the first enrollment period and to suggest hypotheses for future research. Method: We conducted semi-structured interviews with disability community leaders (N = 16) from a maximum variation sample of 10 U.S. states between March and April 2015. Our interdisciplinary team used qualitative description and a series of immersion-crystallization cycles to identify themes. Results: Four themes for people with disability emerged. (1) State-based climate influenced ACA implementation decisions (e.g., Medicaid expansion) and thus individual experiences. (2) Medicaid coverage was viewed as more relevant, affordable and comprehensive than QHPs. (3) Despite expanded coverage, pre-enrollment challenges included accessing enrollment resources (e.g., website, helpline) and obtaining detailed plan information and post-enrollment barriers to needed care due to inadequate provider networks, high co-pays, or visit/service limitations. (4) Navigators with prior experience working with people with disabilities attenuated the identified barriers. Conclusion: Our results depict a complex interplay between the ACA, state efforts and community outreach that influenced people with disabilities' experience. While coverage gains were generally positive, challenges emerged in plan selection and accessing care following enrollment. Attending to contextual factors like state climate and navigator experience as part of ACA implementation may determine health care access, and, ultimately, the health status, of people with disabilities and other population groups.